On barbaric dresses, trousers and tiaras: power and otherness concerning the adoption of foreign dresses by Alexander the Great in Plutarch’s ‘Life of Alexander’ - Biazotto, Thiago do Amaral (Romanitas - Revista de Estudos Grecolatinos, 2018)
Taking the work Life of Alexander, by the Greek biographer and historian Plutarch (c. 45-125 AD), as main source, this article seeks to analyze the otherness and power relations involved in the adoption of foreign dresses by Alexander, as well as to report them to the Roman scenario in with Plutarch may have written.